Pathogenicity and transmission of Morganella morganii in honey bees - Chen, Yijun; Huang, Qiang (PLOS Pathogens, 2025)
Author summary Honey bees are the most abundant commercial pollinator, and beekeepers need to treat Varroa mites twice a year to prevent colony collapse. The mites suck the hemolymph and the bee’s fat body tissue, and vector several viruses. However, the Varroa mite-associated bacteria have been rarely investigated. In this study, we isolated a lethal bacterium, Morganella morganii. A low dosage of M. morganii, which is transmitted through mite feeding, causes high mortality in pupae and adult bees. Our data deepens the knowledge about the bacterial pathogen, vectored by mites.